(untitled) (Texas Journal of Philology, Culture and History, 2022)
The article states about the reorganization of the new system of public administration in independent Uzbekistan, the gradual improvement of the activities of the legislative, executive and judicial authorities, the strengthening of the norms that ensure their independence and equality and mutual restraint. Analyzed the reforms carried out on the way to the formation of a democratic civil society, their goals and practical results.